Dysregulated human Tyrosyl-DNA phosphodiesterase I acts as cellular toxin - Cuya, Selma M. (Oncotarget, 2016)
Tyrosyl-DNA phosphodiesterase I (TDP1) hydrolyzes the drug-stabilized 3’phospho-tyrosyl bond formed between DNA topoisomerase I (TOPO1) and DNA. TDP1-mediated hydrolysis uses a nucleophilic histidine (His(nuc)) and a general acid/base histidine (His(gab)). A Tdp1His(gab) to Arg mutant identified in patients with the autosomal recessive neurodegenerative disease SCAN1 causes stabilization of the TDP1-DNA intermediate. Based on our previously reported His(gab)-substitutions inducing yeast toxicity (Gajewski et al. J. Mol. Biol. 415, 741-758, 2012), we propose that converting TDP1 into a cellular poison by stabilizing the covalent enzyme-DNA intermediate is a novel therapeutic strategy for cancer treatment. Here, we analyzed the toxic effects of two TDP1 catalytic mutants in HEK293 cells. Expression of human Tdp1His(nuc)Ala and Tdp1His(gab)Asn mutants results in stabilization of the covalent TDP1-DNA intermediate and induces cytotoxicity. Moreover, these mutants display reduced in vitro catalytic activity compared to wild type. Co-treatment of Tdp1(mutant) with topotecan shows more than additive cytotoxicity. Overall, these results support the hypothesis that stabilization of the TDP1-DNA covalent intermediate is a potential anti-cancer therapeutic strategy.